2019
DOI: 10.3390/pathogens8040250
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Listeria monocytogenes Isolates from a Poultry-Processing Facility Form More Biofilm but Do Not Have a Greater Resistance to Disinfectants than Sporadic Strains

Abstract: Some strains of Listeria monocytogenes can persist in food-processing environments, increasing the likelihood of the contamination of foodstuffs. To identify traits that contribute to bacterial persistence, a selection of persistent and sporadic L. monocytogenes isolates from a poultry-processing facility was investigated for biofilm-forming ability (crystal violet assay). The susceptibility of sessile cells to treatments (five minutes) with sodium hypochlorite having 10% active chlorine (SHY: 10,000 ppm, 25,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…Exposure to disinfectants imposes a continual stress on bacterial species colonizing FPEs, as these are central to hygiene efforts and food safety. Previous studies have suggested that disinfectant resistance may be a feature of strains encountered, or persisting, in FPEs; this is thought to contribute to the dominance of ST121 and ST204 clonally related strains (Schmitz-Esser et al 2015;Fox et al 2016); however, a positive association with persistence of specific strains in FPEs varies (Kastbjerg and Gram 2009;Fox et al 2011a;Rodr ıguez-Campos et al 2019). A variety of disinfectant resistance markers have been identified in Listeria species, typically comprising efflux pump systems; these include the bcrABC cassette, emrC, emrE, qacA, qacC, qacH and qacED1 determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to disinfectants imposes a continual stress on bacterial species colonizing FPEs, as these are central to hygiene efforts and food safety. Previous studies have suggested that disinfectant resistance may be a feature of strains encountered, or persisting, in FPEs; this is thought to contribute to the dominance of ST121 and ST204 clonally related strains (Schmitz-Esser et al 2015;Fox et al 2016); however, a positive association with persistence of specific strains in FPEs varies (Kastbjerg and Gram 2009;Fox et al 2011a;Rodr ıguez-Campos et al 2019). A variety of disinfectant resistance markers have been identified in Listeria species, typically comprising efflux pump systems; these include the bcrABC cassette, emrC, emrE, qacA, qacC, qacH and qacED1 determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Control of persistent L. monocytogenes strains has been extensively studied (Holah et al, 2002;Romanova et al, 2002;Lundén et al, 2003;Leong et al, 2016;Rodríguez-Campos et al, 2019;Ochiai et al, 2020). A previous study by Vongkamjan et al (2013) b Point estimates of the ratio of odds of having a score (0, 1, 2) when the effect is compared with the odds of having a score of 3. differences in 50 persistent L. monocytogenes strains to 28 different Listeria phages isolated from food processing and dairy production facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Listeria spp. may persist owing to varying biofilm-forming capacity conferring increased resistance to environmental stressors and commonly utilized cleaning and sanitation protocols compared with planktonic isolates (Lou and Yousef, 1996;Lundén et al, 2003;Soni and Nannapaneni, 2010;Fagerlund et al, 2017;Sadekuzzaman et al, 2017;Rodríguez-Campos et al, 2019). Bacteriophage are a promising biocontrol strategy against biofilms and have potential to overcome some of the challenges associated with Listeria control (Moye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms of L. monocytogenes on food contact surfaces have been identified as an important pathway for pathogenic persistence and subsequent product contamination [ 10 , 11 , 12 ]. To this effect, in-depth study of the nature, formation, detection, and elimination of biofilms on surfaces is of great importance due to their impact as a risk factor on outbreaks of foodborne diseases that affect public health [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%